EFFECT OF PREDICT, OBSERVE, AND EXPLAIN (POE) LEARNING MODEL ON STUDENT’S LEARNING ACTIVITIES AND MASTERING OF FOOD DIGESTION SYSTEM CONCEPTS - Adhitian Adhitian; Arwin Achmad; Tri Jalmo (Universitas Lampung, 2013)
The results of interviews with teachers in high school biology class XI Swadhipa Natar, it is known that subjects, especially biology subject matter Digestive System Food is delivered by using the method of discussion. Though this material has special characteristics that examine the mechanisms of complex processes that are difficult to understand, and involve organs that correspond to the structure and function of complex. The purpose of this study is to determine effect of Predict, Observe, Explain And (POE) learning model on student’s learning activities and mastering of Food Digestion System concepts of Swadhipa high school students. This a quasi-experimental strudy used pretest-posttest with non-equivalent dsigned. The sample were students of class XI IPA2 as the experimental group and class XI IPA1 as a control which was selected from the population at random cluster sampling. Data was collected as in percentage form. The students’ actvities observed consists of five (5) abilities of predicting, observing, describing, working together, and making conclusion. The study resulted that POE learning model could enhanced the students’ predicting ability up to 20%, observing ability up to 19%, describing ability up to 24%, abity to work together up to 22,8%, and ability of making onferences up to 16%